Q. 215.0( 3 Votes )

# Prove the followi

Answer : Proof:

Take LHS: Identities used:

(a + b)2 = a2 + b2 + 2ab

a3 – b3 = (a – b) (a2 + b2 + ab)

Therefore,  { cos 2x = cos2 x – sin2 x}  { sin2 x + cos2 x = 1} { sin 2x = 2 sin x cos x}  = RHS

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

If sec (x + α) + RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

0 ≤ x ≤ π aRD Sharma - Mathematics